Pilomatricoma: Clinical, Dermoscopic Findings and Management in 55 Pediatric Patients and Concise Review of the Literature With Special Emphasis on Dermoscopy - Chessa, Marco Adriano; Baracca, Maria Francesca; Rossi, Alice Nadia; Piraccini, Bianca Maria; De Pietro, Vittorio; Marino Picciola, Valentino; Gelmetti, Alessandra; Neri, Iria (Dermatology Practical & Conceptual, 2024)
Introduction: Pilomatricoma is a benign adnexal dermal or subcutaneous tumor derived from immature hair matrix cells.Objectives: The aim of our study is to evaluate clinical and dermoscopic features of pilomatricomas, with a specific focus on pediatric lesions, and to provide a concise review of the existing literature.Methods: A single-center retrospective study was undertaken on 55 patients with a histopathological diagnosis of pilomatricoma referred to the Dermatology Unit, University of Bologna, Bologna, Italy, between 2005 and 2023. Pilomatricomas were retrospectively evaluated relying on clinical and dermoscopic images. A PubMed search was conducted. All the relevant research up to July 31, 2023, was reviewed. We classified the cases as “typical” or “atypical” based on whether they were suspected of being pilomatricomas or not.Results: A total of 55 children with pilomatricomas.were observed and studied. Two patients presented with 2 pilomatricomas, leading to the identification of 58 pilomatricomas. Typical’ pilomatricomas were observed in 79% of cases as nodular and pigmented lesions with one or more colors, ranging from blue-gray to red to yellow/white, evident on clinical examination and even better on dermoscopy. In 21% of cases, pilomatricomas presented in an ‘atypical’ form, which did not allow for a well-founded suspicion, placing them in differential diagnosis with other lesions and therefore requiring histological examination.Conclusions: According to our case series and systematic review of the literature, clinical appearance and dermoscopy may be sufficient to diagnose or suspect pilomatricoma in around 80% of cases, while histological examination is necessary to confirm the diagnosis in the remaining 20% of cases.